Interdependencies between fossil fuel and renewable energy markets: the German biodiesel market - Stefan Busse; Bernard Brümmer; Rico Ihle (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2010)
With this paper, we provide the first quantitative investigation of vertical price transmission in the biodiesel supply chain in Germany with the focus on the developments during the food crisis and the impact of subsidized US biodiesel exports. With the strong promotion of the production and use of biodiesel during the first half of the past decade, the German biodiesel market became the largest national biodiesel market worldwide. This analysis utilizes prices of rapeseed oil, soya oil, biodiesel and crude oil over a sample period covering the rapid growth of the German demand in 2002 until its decline in 2009. The effects of both the market development and different policies on price transmission are analyzed in detail. Due to the numerous changes in the market, a regime-dependent Markov-switching vector error correction model is applied. The results indicate that regimes with differing error-correction behavior govern the transmission process among the various prices. Evidence was found for a strong impact of crude oil price on biodiesel prices, and of biodiesel prices on rapeseed oil prices. However, in both cases, the price adjustment behavior is found to be regime dependent, and the regime occurrence in both market segments shows similar patterns. In relation to crude oil a weak adjustment of biodiesel prices is found to be dominating in the phase of market expansion. This changed from 2007 on when stronger error-correction is found, reflected by a stronger role of the crude oil price developments. In the relationship of biodiesel to the vegetable oils, most of the growth period was dominated by a regime characterized by weak price adjustments. From 2007 on, past own price changes and past changes in soya oil prices had a strong impact particularly on rapeseed oil prices. The biodiesel price development was less important. Reasons for this are substantial changes in the market structure. The biodiesel market developed as an insulated market; biodiesel was mainly produced from rapeseed oil until 2006. Thereafter, biodiesel was increasingly used for blends and sales decreased during the food crisis when agricultural commodity prices rose sharply. At the same time, strong import competition arose from subsidized US B99. The superiority of rapeseed oil for biodiesel production diminished. The uncertainty prevailing in the market from 2007 onwards is reflected by frequent regime changes.
Keywords: C22; Q11; Q18; 330; biodiesel; cointegration; nonlinear vector error correction model; regimedependent model; Markov-switching